Pengaruh Narasi Instagram @DIVISIHUMASPOLRI Terhadap Kesadaran Gen Z Tentang Pengedaran Narkoba - Ghaisany, Nabila Ardelia (Prisani Cendekia Institute, 2025)
In the era of the Industrial Revolution 5.0, the use of social media, especially Instagram, is important in disseminating information and increasing public awareness, especially for Gen Z regarding social issues such as drug trafficking. This study aims to determine the extent to which the narrative delivered through the @divisihumaspolri Instagram account can influence Gen Z's awareness of drug trafficking. This research uses quantitative methods by distributing questionnaires to 100 respondents who are Gen Z followers of the @divisihumaspolri Instagram account. The data obtained was analyzed using regression and correlation analysis with SPSS software. The results showed that there was a significant influence of the @divisihumaspolri Instagram narrative on Gen Z awareness of drug trafficking, with the results of a high correlation coefficient (0.947) indicating a very strong relationship between the @divisihumaspolri Instagram narrative and Gen Z awareness of drug trafficking, then with a coefficient of determination of 89.7%. Respondents rated the narrative as very clear, complete, credible, educative, and visually appealing. This finding is in line with the Uses and Gratification theory as well as previous research that emphasizes the active role of audiences in choosing media and the importance of Instagram as an effective medium in anti-drug campaigns. This shows that social media can be an effective tool to raise public awareness, especially Gen Z about drug trafficking. Therefore, a more interactive and educative communication strategy needs to be implemented to achieve more optimal results.